Highlight selection of radiochemistry and radiopharmacy developments by editorial board - S. Spreckelmeyer; J. Dasilva; C. Decristoforo; R. H. Mach; J. Passchier; G. Carlucci; M. Al Qahtani; A. Duatti; B. T. Cornelissen; J. Engle; A. Denkova; J. J. M. A. Hendrikx; et al. (EJNMMI Radiopharmacy and Chemistry)
Abstract Background The Editorial Board of EJNMMI Radiopharmacy and Chemistry releases a biannual highlight commentary to update the readership on trends in the field of radiopharmaceutical development and application of radiopharmaceuticals. Main body This selection of highlights provides commentary on 24 different topics selected by each co-authoring Editorial Board member addressing a variety of aspects ranging from novel radiochemistry to first-in-human application of novel radiopharmaceuticals. Conclusion Trends in radiochemistry and radiopharmacy are highlighted. Hot topics cover the entire scope of EJNMMI Radiopharmacy and Chemistry, demonstrating the progress in the research field in many aspects.